Different Feeding Percentages on Growth and Survival of Crab Crab (Portunus pelagicus) in Crab House - Faidar, Dzul (JURNAL LEMURU, 2024)
The cultivated crab has slow growth, one of the factors causing it is because the feed given is in the form of trash fish, wich has an incomplete nutritional content, so artificial feed is needed with the appropriate percentage of provision that can increase the growth and survival of crab crab. The purpose of the study was to determine the optimal percentage of artificial feeding in producing growth and 3 replicates consisting of A (5%), B (7%), C (9%) and D (11%) maintained in a crab house. The data obtained were analyzed using analysis of variance (Anova), if the tratments were significantly different, further tests were carried out with the Tukey test to get the best treatment. The results showed the growth of absolute weight, carapace length, carapace width and survival in treatment B (7%).